2009
DOI: 10.1586/eci.09.30
|View full text |Cite
|
Sign up to set email alerts
|

Celiac sprue: a unique autoimmune disorder

Abstract: Celiac sprue (CS) is a gluten-sensitive enteropathy with many autoimmune features. CS involves multiple organs through immune and nonimmune processes, and is frequently associated with other autoimmune disorders. This article reviews the co-occurrence of CS with autoimmune disorders of the cutaneous, nervous, endocrine, musculoskeletal, gastrointestinal and cardiovascular systems. The types of autoimmune disorders associated with CS and the prevalence of CS in other autoimmune disorders are also discussed. A b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 162 publications
(187 reference statements)
0
12
0
3
Order By: Relevance
“…Certainly there was evidence that she had common variable immunodeficiency (CVID) with immunoglobulin deficiencies and poor responses to immunization per her treating rheumatologist. One may argue whether she had celiac sprue at all, however, classic antibodies may be absent in CVID [4,5]. Also, she responded well with decreased stools, weight gain and nutritional improvement of Vitamin K and D. She clearly had osteomalcia with secondary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly there was evidence that she had common variable immunodeficiency (CVID) with immunoglobulin deficiencies and poor responses to immunization per her treating rheumatologist. One may argue whether she had celiac sprue at all, however, classic antibodies may be absent in CVID [4,5]. Also, she responded well with decreased stools, weight gain and nutritional improvement of Vitamin K and D. She clearly had osteomalcia with secondary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Transglutaminase antibodies are characteristic in DH; however a study with immunodeficient mice that received sera from DH patients suggested that circulating antibodies are not pathogenic alone . Using a transgenic mouse model of DH, other authors found similar results , proposing that transglutaminase antibodies may not be sufficient by themselves for the pathology to occur.…”
Section: Extradigestive Manifestations In CD and Ncgs: Linking Diseasmentioning
confidence: 97%
“…The current immunogenetic model for CD does not clarify many of the extradigestive disorders related to CD and NCGS . HLA‐DQ2 and HLA‐DQ8 are the main contributors to CD.…”
Section: Introductionmentioning
confidence: 99%
“…Because CD is associated with other autoimmune diseases [33], it is likely that genes that contribute toward the development of autoimmunity are required for the development of the gluten-sensitive diseases; this theory is supported by the finding that DQ2 and DQ8 only provide 30% to 35% of the familial risk for developing CD [34]. Many of the non-HLA candidate genes that have been identified in a Genomic Wide Association Study (GWAS) are involved in immune function, with some specifically associated with T-cell development of the thymus and other autoimmune diseases, such as type 1 diabetes (T1D) [35].…”
Section: Genetic Predisposition Toward Autoimmunitymentioning
confidence: 99%